THE APPLICATION OF WEB BASED INFORMATION SYSTEM AT MTs AL-IKHLAS FAJAR BULAN, WAY TENONG DISTRICT - Tri Susilowati; Eko Hariyanto (Bakti Nusantara Institute, 2017)
This research’s aim is to simplify the school management data, especially in search, storage, and data reports of school by using website at MTs AL-IKHLAS Fajar Bulan, Way Tenong District, Lampung Regency. In making this application, the researchers used PHP and MySQL. Then, the researchers would analyze to extend web-based information system in that school could assist the administration officers, teachers, and students in applying teaching and learning activity. The method were used in this research were interview and observation. Data collection also used in this research to obtain the required information. The result of this research shows that the use of web-based information system can be a publication in providing a wider range of information to deliver various types of information about that school.